2017
DOI: 10.1253/circj.cj-17-0105
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hydrogen Gas Inhalation on Adverse Left Ventricular Remodeling After Percutaneous Coronary Intervention for ST-Elevated Myocardial Infarction ― First Pilot Study in Humans ―

Abstract: The first clinical study has shown that HI during PCI is feasible and safe and may also promote LV reverse remodeling at 6 months after STEMI. The study was not powered to test efficacy and a further large-scale trial is warranted. (Clinical trials registration: UMIN00006825).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 28 publications
0
71
0
Order By: Relevance
“…It was found that inhalation of hydrogen gas did not reduce the infarct size during the acute phase of MI. However, comparison of cardiac magnetic resonance imaging data obtained 1 week and 6 months after MI showed no change or a decrease in left ventricular stroke volume in the control group, whereas it was increased in the hydrogen gas inhalation group 4. This suggested that inhalation of hydrogen gas during the acute phase of MI suppressed adverse left ventricular remodeling at 6 months after infarction.…”
Section: Clinical Evidencementioning
confidence: 88%
“…It was found that inhalation of hydrogen gas did not reduce the infarct size during the acute phase of MI. However, comparison of cardiac magnetic resonance imaging data obtained 1 week and 6 months after MI showed no change or a decrease in left ventricular stroke volume in the control group, whereas it was increased in the hydrogen gas inhalation group 4. This suggested that inhalation of hydrogen gas during the acute phase of MI suppressed adverse left ventricular remodeling at 6 months after infarction.…”
Section: Clinical Evidencementioning
confidence: 88%
“…While it has been shown that hydrogen gas is effective for preventing ischemia reperfusion injury [1][2][3][4], hydrogen gas is flammable at high concentrations and clinical use is limited by safety considerations. Our previous investigator-initiated clinical trial demonstrated that inhalation of hydrogen gas combined with coronary intervention could inhibit left ventricular remodeling after myocardial infarction [30]. In that trial, the subjects inhaled a gas mixture of hydrogen (1.3%), oxygen, and nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…However, the approximately 60 studies in humans published so far strengthen inhalation of hydrogen gas is being clinically investigated in post-cardiac arrest patients in a large 360-patient multi-centered study with promising preliminary results (Ono et al 2017). Animal studies suggest that H 2 inhalation may be more effective than conventional hypothermia at mitigating the ischemia/reperfusion injury following cardiac resuscitation (Katsumata et al 2017). Table 2 summarizes the known studies on hydrogen administration and exercise in humans and animals, illustrating hydrogen's potential benefit in exercise medicine and sports performance.…”
Section: Human Studies With H 2 Administrationmentioning
confidence: 99%